2020
DOI: 10.1515/chem-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Saliva proteomic analysis reveals possible biomarkers of renal cell carcinoma

Abstract: Early diagnosis is a key to improve the prognosis of renal cell carcinoma (RCC); however, reliable RCC biomarkers are lacking in clinical practice. In this study, we used isobaric tags for relative and absolute quantification-based mass spectrometry to identify salivary proteins as biomarkers for the diagnosis of RCC. The objective of this study is to discover biomarkers from saliva by utilizing high-throughput quantitative proteomics approaches. Saliva proteins from 124 RCC patients and healthy individuals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…Следует также отметить возможность использования не только плазмы, но и слюны для детекции онкомаркеров [98], и Hp в том числе [99]. Например, сравнительный протеомный анализ выявил достоверное превышение (в 2,5 раза) уровня Hp в слюне у пациентов с раком почки по сравнению со здоровыми донорами [99].…”
Section: гаптоглобин и его протеоформы как потенциальные биомаркеры заболеванийunclassified
See 1 more Smart Citation
“…Следует также отметить возможность использования не только плазмы, но и слюны для детекции онкомаркеров [98], и Hp в том числе [99]. Например, сравнительный протеомный анализ выявил достоверное превышение (в 2,5 раза) уровня Hp в слюне у пациентов с раком почки по сравнению со здоровыми донорами [99].…”
Section: гаптоглобин и его протеоформы как потенциальные биомаркеры заболеванийunclassified
“…Следует также отметить возможность использования не только плазмы, но и слюны для детекции онкомаркеров [98], и Hp в том числе [99]. Например, сравнительный протеомный анализ выявил достоверное превышение (в 2,5 раза) уровня Hp в слюне у пациентов с раком почки по сравнению со здоровыми донорами [99]. Авторы этого исследования делают вывод о том, что их экспериментальные результаты указывают на возможность использования гаптоглобина наряду с белком S100A9 в качестве потенциальных неинвазивных биомаркеров для диагностики рака почки.…”
Section: гаптоглобин и его протеоформы как потенциальные биомаркеры заболеванийunclassified
“…Saliva is one of the complex and important multi-constituent body fluids that reflects a wide variety of physiological knowledge due to its contents extensively supplied by the blood. Moreover, a saliva-based diagnosis has been drawing attention in the diagnosis of systemic diseases such as renal cancers, due to the source, composition, function, and interaction of saliva with the substances that make up the plasma [ 29 , 30 ]. In the present study, besides blood components and urine, we also demonstrated the potential of saliva as a non-invasive potential media for RCC diagnosis, especially in chRCC.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that it is possible to use not only plasma but also saliva for the detection of tumor markers [ 98 ], including haptoglobin [ 99 ]. For example, comparative proteomic analysis revealed a significant excess (2.5 times) of the level of haptoglobin in saliva in patients with kidney cancer compared with healthy donors [ 99 ].…”
Section: Haptoglobin and Its Proteoforms As Potential Biomarkers Of Diseasesmentioning
confidence: 99%
“…It should also be noted that it is possible to use not only plasma but also saliva for the detection of tumor markers [ 98 ], including haptoglobin [ 99 ]. For example, comparative proteomic analysis revealed a significant excess (2.5 times) of the level of haptoglobin in saliva in patients with kidney cancer compared with healthy donors [ 99 ]. The authors of this study conclude that their experimental results indicate the possibility of using haptoglobin along with the S100A9 protein as potential non-invasive biomarkers for the diagnosis of kidney cancer.…”
Section: Haptoglobin and Its Proteoforms As Potential Biomarkers Of Diseasesmentioning
confidence: 99%